How much is a criminal law legal instrument to respond to the challenges climate change? (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
This paper explores both the possibility and the suitability of assigning Criminal Law a supplementary role as a legal response to global warming. To this end, this paper deals with the application of article 325 of the Spanish Penal Code with a view to impose a criminal sanction for certain infringements of Administrative Law onclimate change and also with the creation of a specific criminal offence regarding the damage to the climate system.
Keywords: Criminal Law; climate change; article 325 of the Penal Code